2020
DOI: 10.1371/journal.pone.0241973
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale and structure of complex life cycle trematode parasite communities in streams

Abstract: By considering the role of site-level factors and dispersal, metacommunity concepts have advanced our understanding of the processes that structure ecological communities. In dendritic systems, like streams and rivers, these processes may be impacted by network connectivity and unidirectional current. Streams and rivers are central to the dispersal of many pathogens, including parasites with complex, multi-host life cycles. Patterns in parasite distribution and diversity are often driven by host dispersal. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…For example, Theron et al (1978) sampled along a small canal in Guadeloupe and found that infection prevalence with Schistosoma mansoni in Biomphalaria glabrata snails increased downstream. However, other studies have found the opposite trend, with higher parasitism upstream in headwater sites (Zemmer et al, 2020), although the mechanism for this is unclear. Flow may explain some of the variation in infection prevalence in our system since flow rate was unidirectional (albeit seemingly slow), and may have caused eggs or miracidia (that infect snails) to accumulate downstream.…”
Section: Discussionmentioning
confidence: 86%
“…For example, Theron et al (1978) sampled along a small canal in Guadeloupe and found that infection prevalence with Schistosoma mansoni in Biomphalaria glabrata snails increased downstream. However, other studies have found the opposite trend, with higher parasitism upstream in headwater sites (Zemmer et al, 2020), although the mechanism for this is unclear. Flow may explain some of the variation in infection prevalence in our system since flow rate was unidirectional (albeit seemingly slow), and may have caused eggs or miracidia (that infect snails) to accumulate downstream.…”
Section: Discussionmentioning
confidence: 86%
“…alias ‘ Sanguinicola ’ sp. from the USA (Zemmer et al ., 2020) formed a strongly supported subclade with P . occidentalis , indicating that it is a species of Pseudosanguinicola .…”
Section: Discussionmentioning
confidence: 97%
“…from Vietnam; Pseudosanguinicola occidentalis Warren and Bullard, 2023 and unidentified species from the USA (Warren et al ., 2023; Warren and Bullard, 2023). In addition, DNA data are available for cercariae of 12 sanguinicolids from freshwater gastropods from Australia, East Africa, Poland and USA (Olson et al ., 2003; Brant et al ., 2006; Zemmer et al ., 2020; Preston et al ., 2021; Cutmore et al ., 2023). However, the identities of some of the cercariae whose sequences are available remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…It may also occur through human-mediated movements, although no information is available regarding this possibility. Therefore, it is more logical to expect a correlation with the population genetic structure of seabass, the most mobile host in the trematode life cycle (Zemmer et al ., 2020). Two distinct genetic population units, one in the Atlantic area and another in the Mediterranean, have been previously identified for seabass (Souche et al ., 2015), with a slight genetic differentiation in the Atlantic area observed south of the Strait of Gibraltar (Morocco) attributed to a hybrid zone between 2 evolutionary lineages (Lemaire et al ., 2005; Vandeputte et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%